2020
DOI: 10.1038/s42255-020-0181-1
|View full text |Cite
|
Sign up to set email alerts
|

MESH1 is a cytosolic NADPH phosphatase that regulates ferroptosis

Abstract: S tringent response is the main strategy used by bacteria to cope with fluctuating nutrient supplies and metabolic and oxidative stresses 1,2 . This process rapidly redirects energy from cell proliferation toward stress survival by reduction of biosynthesis, conservation of ATP and blockage of GTP production 3 . The stringent response is triggered by the accumulation of the bacterial 'alarmone' (p)ppGpp (guanosine tetra-or penta-phosphate, shortened as ppGpp below) through the regulation of ppGpp synthetases a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 40 publications
7
124
0
Order By: Relevance
“…In addition, pharmacogenomic analyses identified NAPDH as a robust determinant of ferroptosis [48], probably by regenerating GSH. Consistently, we have found that MESH1, the metazoa homolog of SpoT, is the first cytosolic NADPH phosphatase [49] whose induction is responsible for the NAPDH depletion during ferroptosis [50].…”
Section: Gpx4 and Fsp1 Mediate Two Ferroptosis Protection Pathwayssupporting
confidence: 73%
“…In addition, pharmacogenomic analyses identified NAPDH as a robust determinant of ferroptosis [48], probably by regenerating GSH. Consistently, we have found that MESH1, the metazoa homolog of SpoT, is the first cytosolic NADPH phosphatase [49] whose induction is responsible for the NAPDH depletion during ferroptosis [50].…”
Section: Gpx4 and Fsp1 Mediate Two Ferroptosis Protection Pathwayssupporting
confidence: 73%
“…No synthetases of (p)ppGpp have been yet found in animal cells, but an enzyme capable of hydrolysis of (p)ppGpp, called Mesh1 has been detected in worms, flies, and humans ( Sun et al, 2010 ). The human version of Mesh1 has been found to hydrolyze (p)ppApp and NADPH as well as (p)ppGpp ( Ding et al, 2020 ; Jimmy et al, 2020 ). Whether NADPH is the bona fide substrate of Mesh1 is still a matter of debate, considering that the Drosophila version did not reduce the cellular pools of NADPH when expressed in Escherichia coli ( Zhu and Dai, 2019 ).…”
Section: (P)ppgpp Many Ways To Transfer a Pyrophosphate Group Back Amentioning
confidence: 99%
“…Recently, is has been suggested that that the human MESH1 enzyme is an NADPH phosphatase that degrades NADPH to NADH (Ding et al, 2020). Since in the coupled assay for pppNpp hydrolysis NADPH accumulation is being followed (see Figure 2), this could have a potential impact on the obtained results.…”
Section: Nadph Does Not Seem To Be Hydrolyzed By Mesh1 Mesh1 or Sahmentioning
confidence: 99%